PEMETAAN QOS DENGAN METODE INTRINSIK BERBASIS STANDAR HATTINGH PADA JARINGAN WERELLESS UGM-HOSTPOT PPTIK UGM - Nugroho, M. Agung; Utami, Emma; Sudarmawan, Sudarmawan (Universitas Respati Yogyakarta, 2013)
The high usage of wireless network will affect the level of data traffic. if there are multiple users to request a connection with the limited capacity of the connection between the user simultaneously then it will wait for their turn in the connect. The simple solution for institutions by adding capacity or bandwidth. But by adding bandwidth, the cost is also quite large. End-to-end monitoring method allows a provider to determine the quality of service QoS using actual data from the availability of services. This information in turn can be useful to know the characteristics of the use of the service, so that the results of monitoring in the form of hotspot service profile may be a reference to determine the user's perception. The final results of this research is profile of network quality service of UGM-Hotspot on PPTIK UGM. It could be a reference to improve QoS, and reference for making policy-based network management.Â Keyword : QoS, hattingh standard, end-to-end monitoring, wireless network, quality of services